Effectiveness of CBT Approach in Group Counseling to Reduce Anxiety in Completing Thesis in Final Year Students of UNIPAR Jember - Fathullah, Abdusy Syahid; Rahmawati, Weni Kurnia; Mawaddati, Ika Romika (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Effectiveness of CBT Approach in Group Counseling to Reduce Anxiety in Completing Thesis in Final Year Students of UNIPAR Jember. This study aims to test the effectiveness of the Cognitive Behavioral Therapy (CBT) approach in group counseling to reduce anxiety of final year students in completing their thesis at Universitas PGRI Argopuro (UNIPAR) Jember. Anxiety related to thesis is a common problem faced by final year students, which can hinder the academic process and completion of studies. CBT as a psychotherapy approach has been proven effective in overcoming various anxiety disorders. This study used an experimental design with pre-test and post-test methods to measure changes in students' anxiety levels before and after group counseling intervention using the CBT approach. The sample consisted of 48 final year students of UNIPAR Jember who were selected purposively, and the research procedure included providing group counseling sessions with CBT for several weeks. The results showed a significant decrease in anxiety levels after participating in CBT-based group counseling, which confirmed the effectiveness of this approach in helping students overcome anxiety related to thesis. This study contributes to the field of educational psychology by showing that the CBT approach in group counseling is effective in reducing anxiety of final year students in completing their thesis, so that it can be applied as an intervention strategy in academic environments.Keywords: Effectiveness, CBT Approach, Group Counseling, Anxiety, Completing Thesis, Students